2009
DOI: 10.1007/978-1-4419-1603-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A in Cancer Therapies Preclinical Results

Abstract: Studies in animal models showed that the antitumoral effect of LPS and of their biologically active moiety, lipid A, is indirect and relies on the induction of an immune response both innate and specific, leading to cytokine production. They also affect tumor development by inhibiting tumor blood flow and induce necrosis as well as apoptosis of tumor cells. Lipids A have been tested in animals, either alone or as adjuvant in therapeutic vaccines. The efficacy of treatments depends on the type of molecule and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“… 4 6 Inappropriate regulation of TLR4 signaling and ensuing overactivation of innate immune system was shown to contribute to the development and pathogenesis of chronic inflammatory, autoimmune, and infectious diseases, including asthma, arthritis, multiple sclerosis, inflammatory bowel disease, and cancer. 7 10 …”
mentioning
confidence: 99%
“… 4 6 Inappropriate regulation of TLR4 signaling and ensuing overactivation of innate immune system was shown to contribute to the development and pathogenesis of chronic inflammatory, autoimmune, and infectious diseases, including asthma, arthritis, multiple sclerosis, inflammatory bowel disease, and cancer. 7 10 …”
mentioning
confidence: 99%
“…However, adjunct treatment per se, unlike cidofovir, did not activate NK cells and triggered differentiation of B cells into antibody-secreting plasma cells. Aluminum hydroxide and MPL are mostly used as adjuvants in cancer vaccines though various lipids A have been used to treat animals with established tumors [ 65 ]. In animal models, the antitumor effect of LPS (lipopolysaccharide) and of the biologically active moiety, lipid A, was shown to be indirect and to rely on the induction of both an innate and specific immune response, leading to cytokine production [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies also suggested a possible implication of TLR4 in cardiovascular disorders [ 54 ] and Alzheimer desease – associated pathology [ 55 ]. Therapeutic down-regulation of the TLR4 signaling is believed to be beneficial for treatment of numerous chronic and acute inflammatory diseases such as asthma [ 51 ], arthritis [ 52 ], influenza [ 50 ], and cancer [ 56 ]. Furthermore, TLR4 has been shown to link the innate and adaptive immunity [ 57 58 ], underscoring stimulation of the TLR4·MD-2 complex by non-toxic TLR4-specific ligands as an apparent tactic for development of novel vaccine adjuvants [ 59 61 ].…”
Section: Introductionmentioning
confidence: 99%